Overview: Recent progress in three-dimensional atom probe instruments and applications - Cerezo, A; Lozano-Perez, S; Sha, G; Smith, G; Clifton, P; Panayi, P (2007)
Over the last few years there have been significant developments in the field of three-dimensional atom probe (3DAP) analysis. This article reviews some of the technical compromises that have led to different instrument designs and the recent improvements in performance. An instrument has now been developed, based around a novel reflectron configuration combining both energy compensation and focusing elements, that yields a large field of view and very high mass resolution. The use of laser pulsing in the 3DAP, together with developments in specimen preparation methods using a focused ion-beam instrument, have led to a significant widening in the range of materials science problems that can be addressed with the 3DAP. Recent studies of semiconductor materials and devices are described. © MICROSCOPY SOCIETY OF AMERICA 2007.